The Students’ Views on Blended Learning Used on Reading Skills: A Case Study in One of Institutes in Jambi - Safitri, Elsa; Erniyati, Yelni (JELITA, 2025)
This study aims to explore students' views on blended learning in developing reading skills, identifying perceived pros and cons. The study employed a qualitative research design using a constructivist approach for data collection and coding for analysis. Four students from an Islamic educational institution in Jambi participated, chosen for their diverse backgrounds to gain a comprehensive perspective. Semi-structured interviews focused on how blended learning affected their reading comprehension. The findings show that blended learning, which combines online and face-to-face teaching, offers benefits such as flexibility, access to materials at any time, and increased self-directed learning. However, students also reported limitations, including technical issues, lack of interpersonal interaction, and challenges in maintaining motivation. This study concludes that while blended learning has the potential to improve independent learning and reading skills, effective implementation is needed to overcome existing barriers and improve learning outcomes in higher education.